Learning Motivation and Its Relationship with Academic Achievement Among Female Students of the College of Education at the University of Hail - Almutawea, Malkah Murdi; Alshammari, Bashayr Nawaf; Alsuhaifi, Abrar Eid (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the level of learning motivation and its relationship with academic achievement among female students at the College of Education, University of Hail. Using a descriptive correlational approach, the study was conducted on a randomly selected sample of 209 students. Data were collected through a validated learning motivation scale developed by Aziz (2021), which assesses three dimensions: cognitive motivation, achievement motivation, and academic ambition. The results revealed that students demonstrated a very high level of motivation, particularly in cognitive and achievement-related aspects, while academic ambition was rated as high. In terms of academic performance, the students’ GPAs indicated a “very good” level of achievement. However, statistical analysis showed a weak, positive, and non-significant correlation between learning motivation and academic achievement, suggesting that while motivation is an important factor, it does not solely determine academic outcomes. The study concludes by recommending the development of educational strategies that enhance students’ motivation and foster a learning environment that supports comprehensive academic success.